Compliance with Procalcitonin Algorithm Antibiotic Recommendations for Patients in Medical Intensive Care Unit. Issue 2 (3rd February 2017) - Ammar, Abdalla A.; Lam, Simon W.; Duggal, Abhijit; Neuner, Elizabeth A.; Bass, Stephanie N.; Guzman, Jorge A.; Wang, Xiao‐Feng; Han, Xiaozhen; Bauer, Seth R.
Abstract : Study Objectives: To describe compliance with antibiotic recommendations based on a previously published procalcitonin (PCT)‐guided algorithm in clinical practice, to compare PCT algorithm compliance rates between PCT assays ordered in the antibiotic initiation setting (PCT concentration measured less than 24 hours after antibiotic initiation or before antibiotic initiation) with those in the antibiotic continuation setting (PCT concentration measured 24 hours or more after antibiotic initiation), and to evaluate patient‐ and PCT‐related factors independently associated with algorithm compliance in patients in the medical intensive care unit (MICU). Design: Single‐center retrospective cohort study. Setting: Large MICU in a tertiary care academic medical center. Patients: A total of 527 adults admitted to the MICU unit over a 2‐year period (November 1, 2011–October 31, 2013) who had a total of 957 PCT assays performed. PCT assays whose results were determined in the MICU were allocated retrospectively to either the initiation setting cohort or the continuation setting cohort based on timing of the PCT assay. Measurements and Main Results: Each PCT assay was treated as a separate episode. Antibiotic regimens were compared between the 24‐hour periods before and after the results of each PCT assay and evaluated against an algorithm to determine compliance. Clinical, laboratory, PCT‐related, and microbiologic variables were assessed during the 24‐hour period after the PCT assay results to determine their influence on PCT algorithm compliance. A larger proportion of PCT episodes occurred in the initiation setting (540 [56.4%]) than in the continuation setting (417 [43.5%]). Overall, compliance with PCT algorithm recommendations was low (48.5%) and not significantly different between the initiation setting and the continuation setting (49.1% vs 47.7%, p=0.678). No patient‐related or PCT‐related factors were independently associated with PCT algorithm compliance on multivariable logistic regression. Conclusion: Compliance with PCT algorithm antibiotic recommendations in both the initiation and continuation settings was lower than that reported in published randomized studies. No factors were independently associated with PCT algorithm compliance. Institutions using PCT assays to guide antibiotic use should assess compliance with algorithm antibiotic recommendations. Inclusion of a formalized antimicrobial stewardship program along with a PCT‐guided algorithm is highly recommended.